PENGUATAN KUALITAS GURU MADRASAH MELALUI WORKSHOP PENATAAN KURIKULUM, ADMINISTRASI DAN MANAGEMENT - Eki Agustin; Nurul Hidayah; Siti Sopiah (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
One form of teacher professionalism is being able to maintain the quality of administration and management which is summarized through the madrasah diniyah takmiliyah Awaliyah curriculum program. Therefore, teachers should continue to learn about the appropriate administrative procedures, accompanied by physical evidence, namely the curriculum. Currently administrative staff is very important because there are so many legal rules that require every institution to follow the applicable provisions. Completeness of madrasa documents is needed to support madrasas to progress and develop. Workshop activities can motivate madrasa managers and educators to maximize madrasa administration. Have insight in planning learning or curriculum formulation. Management that is active and not passive will be able to maximize the programs that have been designed to be implemented.